Role of the Personal Promotional Factors Determining Agri-entrepreneurship Performance in Surkhet District - Pulami, Hasta Bahadur (Researcher CAB: A Journal for Research and Development, 2023)
This study focuses on the role of personal promotional factors determining agri-entrepreneurship performance, with a sample size of 405 respondents from infinite small and medium agri-entrepreneurship of Surkhet district. The data were collected using structured questionnaire containing multiple choice questions and Likert scale questions. The survey was conducted in Kartik 2079 on active agri-entrepreneurs. The factors determining agri-entrepreneurship performance were grouped into three main variables, i.e., self-efficacy (SE), creativity and innovation level (CI), and risk preference level (RP). Modeling of multiple regression analysis was used in inferential statistics. The result showed that agri-entrepreneurs’ self-efficacy level, creativity and innovation level, and risk preference level have a significant impact on the agri-entrepreneurship performance. Based on univariate analysis self-efficacy has the most significant effect on agri-entrepreneurship performance followed by creativity and innovation skill; and risk preference level. Although variables are jointly regressed in bivariate regression, coefficients are decreased. This study concluded that agri-entrepreneurship performance of agri-entrepreneurs of Surkhet district is more determined by self-efficacy level. Agri-entrepreneurs in the field of agriculture could consider this factor to have better choices while entering or continuing with their agri-entrepreneurships.